The first official measurement of 11C in the SIRTI. (December 2019) - Galea, R.; Michotte, C.; Nonis, M.; Moore, K.; Gamal, I. El; Keightley, J.; Fenwick, A.
Abstract: In the summer of 2017, the Système International de Référence Transfer Instrument (SIRTI) of the Bureau International des Poids et Mesures (BIPM) was hosted by the National Research Council of Canada (NRC) in Ottawa, Canada. This SIRTI visit was unique in many aspects. It was the first visit of the SIRTI to Canada. NRC was the first National Metrological Institute (NMI) to perform comparisons of four isotopes ( 99m Tc, 18 F, 64 Cu and 11 C) during a single two-week period. Finally, this was the first official measurement of 11 C in the SIRTI. The NRC had performed a primary standardization of 11 C in February of 2017 and calibrated its Secondary Standard Ionizing Radiation Chamber System (SSIRCS) in preparation for the SIRTI comparison. Two primary Liquid Scintillation methods (CIEMAT/NIST and TDCR) were employed and the results agreed. The stock material was received from a local cyclotron in the form of a 11 C-labelled sodium acetate (NaC2 H3 O2 ). Three ampoules were prepared for the purposes of comparison; one concentrated from the bulk material and two derived from a single dilution. Some inconsistency was evident due to a weighing problem for one of the ampoules containing the diluted solution, whose measurements were excluded from the analysis. The other two ampoules' results were consistent within their respective uncertainties. The SIRTI was very stable and the final BIPM report will detail the stability checks, performance and behaviour of the SIRTI during its measurement campaign in Canada. There is still no Key Comparison Reference Value (KCRV) for 11 C as NRC is the first participant. However, during a test of the SIRTI at NPL in 2014, an equivalent SIRTI activity was measured as 9.87(5) kBq which was consistent with MonteCarlo predictions for 11 C in the SIRTI of 9.867(15) kBq. The NRC SIRTI equivalent activity for 11 C agrees within uncertainty with these results. This offers encouragement to other NMIs to request a 11 C comparison given the consistency of experimental results from NRC and test results from the National Physical Laboratory, UK (NPL) and the BIPM. Finally a half-life measurement was determined from the NRC measurement of multiple half-lives of a 11 C ampoule and was found to be 20.332(40)min. From the SIRTI measurements at NRC, the half-life was derived as 20.328(13) min. This is smaller but consistent with the DDEP recommended value of 20.361(23)min. Highlights: 11 C was measured in the SIRTI for the first time. NRC hosted the SIRTI for the first time. Measurements of the 11 C half-life were consistent with literature.